Stabilization of Gypsum Clay Soil by Adding Lime - Ikram Saidate; Abd Elmajid Berga; Tayeb Rikioui (Salehan Institute of Higher Education, 2022)
Often, the temperature and water variation exist in semi-arid areas of a clayey soil leads to vertical and horizontal settlements, cracks in the soil and in general disorder to the building installed on this soil. The objective of this work is to stabilize the local gypsum clay soil, which poses problems at the level of self-construction built on it. Chemical soil stabilization can improve soil properties. In fact, adding natural lime to these clays can provide an ideal solution for stabilizing them through interesting modifications to their geotechnical properties throw the experimental tests on both unstabilized and stabilized soil samples by adding lime in quantities of 2, 4, and 6%, in percentages by the soil's weight, prepared at room temperature, The unconfined compressive strength (UCS) at different curing ages is measured, The results obtained provide a significant increase in compressive strength and modulus of Elasticity which allow better qualities and improve strength parameters throughout any phase of earthwork construction design that leads to strengthening subgrades, reducing the thickness, and, as a result, low construction costs. The results of the study show that (1) for the best utilization effect, the optimum percentage of lime is 6%; (2) the UCS is 3.23 times of the pure soil after curing of 28 days under the optimum percentage of lime; (3) the curing age has a significant effect on strength; (4) the main reason for the strength increase of the modified soil is that the crystal produced by the pozzolanic activity fills the pores of the soil. The ideal percentage is 6% lime treatment with a resistance of 2.3 MPa and 135.60 MPa the value of elasticity modulus at 28 days. Doi: 10.28991/CEJ-2022-08-11-010 Full Text: PDF